Recent advancements on superabsorbent polymers to produce controlled release urea (short review) - Azeem, B. (Trans Tech Publications Ltd, 2014)
Controlled release urea (CRU) is produced to avoid nitrogen losses caused by volatilization, leaching and denitrification. Superabsorbent polymer materials have recently caught the attention of research circles to be used as coating materials to produce CRU. This review portrays recent advancements on the use of superabsorbent polymer materials to produce CRU with special focus on release experiments. Â© 2014 Trans Tech Publications, Switzerland.